Effects of low and high temperatures on infectivity of Cryptosporidium muris oocysts suspended in water - Neumayerová, Helena; Koudela, Bretislav (Veterinary parasitology, 2008)
Cryptosporidium muris oocysts suspended in 200 microl of water were pipetted into plastic microcentrifuge tubes which were stored at 4 degrees C or frozen at -5 degrees C for 1, 3, 5, 7, and 10 days and at -20 degrees C for 1, 3, 5, and 8h, respectively. Other samples of C. muris oocysts suspended in water were heated in the metal block of a thermal DNA cycler. Block temperatures were set at 5 degrees C incremental temperatures from 40 to 70 degrees C. At each high temperature setting microcentrifuge tubes containing C. muris oocysts were exposed for 1 min. Both, frozen and heated oocyst suspensions as well as untreated control oocyst suspensions were then inoculated into each of four ICR mice by gastric intubation. Untreated, freeze-thawed or heated oocysts were considered infectious when oocysts of C. muris were found microscopically in the faeces of mice after inoculation. All inoculated mice that received oocysts frozen at -5 degrees C for 3, 5, 7, and 10 days and -20 degrees C for 1, 3, 5, and 8h had no oocysts in faeces. In contrast, C. muris oocysts frozen at -5 degrees C for 1 day remained infective for inoculated mice. Our results also indicated that when water containing C. muris oocysts was exposed at a temperature of 55 degrees C or higher for 1 min, the infectivity of oocysts was lost.
Keywords: Feces; Male; Freezing; oocysty; kryptosporidióza; voda; Cryptosporidiosis; Biological Assay; mužské pohlaví; biotest; Water; Mice, Inbred ICR; zmrazování; Time Factors; Oocysts; Animals; zvířata; vysoká teplota; časové faktory; myši; myši inbrední ICR; Cryptosporidium; Mice; feces; nízká teplota; Hot Temperature; Cold Temperature